Influence of Fan Attachment and Attitude towards Impulsive BTS Meal Purchasing Interest among Army (BTS Fans) - Dewi Deniaty Sholihah; Nurkholis Majid (Journal of Economics, Business, and Government Challenges, 2023)
This research aims to examine the factors that cause impulse buying by Army (BTS fans) which are influenced by attachment and attitude towards the product. The research was conducted by involving BTS fans who are members of groups affiliated with Kapanlagi.com media. The sample in the study was 97 people, representing a response rate of 97% of the target sample. Data analysis was conducted using PLS 3.0 and showed that fan attachment can trigger impulsive buying activity carried out by Army. In addition, attachment also has an impact on improving the view of the product by having a label with the BTS logo as a brand. However, the attitude towards the product does not necessarily lead to impulse buying interest because it requires attachment factors to build spontaneous purchases